THE QUR'AN IN RITES: HISTORICAL ANALYSIS AND ACCULTURATION OF JAVANESE CULTURE - Samsul Ariyadi (PT. Jurnal Center Indonesia Publisher, 2025)
This article examines the transformation of the meaning of the Quran in the context of death rites and death commemorations in Javanese society, especially in Central Java and Yogyakarta, during the period 2000–2023. This research approach is qualitative by utilizing ethnographic data, archival studies, ritual documentation, and in-depth interviews with ritual practitioners. The use of the Quran, which was originally a sacred Islamic text with normative content, has undergone a transformation of meaning when adapted into traditional Javanese rites. The process of cultural acculturation that occurred illustrates the dynamics between ancestral traditions and Islamic values, which provide space for the reinterpretation of religious symbols by local communities (Anderson, 2003; Suryadi, 2011). The historical analysis method and the theory of cultural transformation proposed by Clifford Geertz are used to explain the evolution of the use of the sacred text and highlight the role of ritual as a medium for negotiating meaning between cultures. The results of the study show that the insertion of Quranic verses into Javanese mantras not only functions as a sacred element, but also as a tool for social legitimacy and cultural identity of the Javanese people. This finding opens up opportunities for further study on the integrative role of ritual in shaping religious and cultural identity in Indonesia.